Macro and microscopic visual imaging tools to investigate metal reducing bacteria in soils. Issue 1 (21st January 2021) - Scott, Brian; Baldwin, Andrew H.; Yarwood, Stephanie; Castañeda, Carmen; Latorre, Borja; Rabenhorst, Martin C.
Abstract: Indicator of Reduction In Soils (IRIS) technology is an important tool for identifying hydric soils, but it does not allow the user to monitor in real time. IRIS uses metal‐oxide coatings on a polyvinyl chloride surface that, under anaerobic conditions, are removed to varying degrees over a 4‐wk incubation period, during which time the user is not cognizant of the outcome. We document the viability of an alternative IRIS approach using clear‐IRIS tubes, made from cellulose acetate butyrate, that can be continuously monitored in situ with a Wi‐Fi–enabled video camera. This work shows that IRIS and clear‐IRIS tubes are statistically equivalent. Manganese‐oxide coated clear‐IRIS tubes correlated well with IRIS tubes ( r = .79) and ferrous‐oxide had a high correlation ( r = .97). A time‐series analysis showed that rain‐driven soil saturation induced IRIS metal‐oxide reduction and controlled the rate. Clear‐IRIS tubes enable remote sensing of metal‐oxide removal over time. Core Ideas: Clear‐IRIS tubes perform the same as PVC IRIS tubes. Microbial biofilms did not form on metal‐oxide surfaces. Soil saturation determines the rate of IRIS reaction.